Predicting nurses' turnover intentions by demographic characteristics, perception of health, quality of work attitudes. Issue 1 (18th June 2013) - Al‐Hussami, Mahmoud; Darawad, Muhammad; Saleh, Ali; Hayajneh, Ferial Ahmed
<x xml:space="preserve">Abstract</x> The purpose of this paper is to examine the impact of demographic variables, organizational commitment levels, perception of health and quality of work on turnover intentions. A self‐reported cross‐sectional survey design was used to collect data from Jordanian registered nurses who were working between June 2011 and November 2011. The findings showed strong effects of the quality of work, perception of health and normative organizational commitments on turnover intentions. This study sheds the light on the important work outcomes in health‐care organizations. Increasing nursing quality of work and normative organizational commitment are good strategies for reducing turnover intentions.